Progress in Cryptology - LATINCRYPT 2012 2nd International Conference on Cryptology and Information Security in Latin America, Santiago, Chile, October 7-10, 2012, Proceedings - Hevia, Alejandro; Neven, Gregory (Security and Cryptology ;, 2012)
This book constitutes the proceedings of the 2nd International Conference on Cryptology and Information Security in Latin America, LATINCRYPT 2012, held in Santiago, Chile, on October 7-10, 2012. The 17 papers presented together with four invited talks and one student poster session were carefully reviewed and selected from 47 submissions. The papers are organized in topical sections on elliptic curves, cryptographic protocols, implementations, foundations, and symmetric-key cryptography.